The political economy of Malaysian federalism: Economic development, public policy and conflict containment - K. S. Jomo; Wee Chong Hui (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Conflicts within the Malaysian federation have been rooted in socio-economic disparities and the struggle for control of natural resource rents, which State Governments previously had exclusive control over, as originally provided for by the federal constitution. The advance of fiscal centralization since then has also aggravated federal-state tensions, which have been relatively ignored due to the long-standing Malaysian pre-occupation with inter-ethnic tensions. Inter-regional resource transfers and central fiscal and political dominance have been used to undermine the more independent State Governments, especially those held by opposition parties. While the federal government is clearly dominant, central control over the State Governments has varied, especially in Sabah and Sarawak, with the continued hegemony of the national ruling coalition depending on successfully combining the carrot with the stick. – conflict ; fiscal policy ; regional policy ; Malaysia
Keywords: O1; R58; O53; O23; 330; Finanzpolitik; Föderalismus; Regionalpolitik; Malaysia